2005
DOI: 10.1177/0092055x0503300201
|View full text |Cite
|
Sign up to set email alerts
|

Computer Mediated Communication and Student Learning in Large Introductory Sociology Classes

Abstract: Over the past several years, scholars of teaching and learning have demonstrated the potential of collaborative learning strategies for improving student learning. This paper examines the use of computer-mediated communication to promote collaborative student learning in large introductory sociology courses. Specifically, we summarize a project we conducted during the 2000-2001 academic year in which we added online collaborative learning activities to the curriculum of two large sections of introductory socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…The main reasons for this reluctance include (but are not restricted to) the following (Brindley et al, 2009;Piezon & Ferree, 2008;Wright & Lawson, 2005):…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for this reluctance include (but are not restricted to) the following (Brindley et al, 2009;Piezon & Ferree, 2008;Wright & Lawson, 2005):…”
Section: Introductionmentioning
confidence: 99%
“…It highlights the need to educate children and young people about the benefits, risks and responsibilities of using information technology and to develop safer online behaviours both in and out of schools (Wright and Lawson, 2005).…”
Section: E-safety Concerns For Young Peoplementioning
confidence: 99%
“…Perhaps more significantly, Homan and Poel (1999) concluded that most dissatisfied students did not know how to work effectively in groups. Researchers also found high levels of dissatisfaction in online learners required to participate in group work with complaints focused on time and logistical barriers to collaboration as well as increased difficulty in ensuring participation of all members (Brindley & Walti, 2009: Fletcher, Tobias & Wisher, 2007Piezon &Ferree, 2008: Wright andLawson, 2005). Previous group experiences, the quality of guidance and instruction (Colbeck, Campbell, & Bjorklund, 2000), the method of group assessment (Lejk, Wyvill, & Farrow, 1996), and the system of group formation (Daly & Worrell, 1993;Feichtner & Davis, 1985) all contribute to determining how successful group work will be in generating positive learning experiences for students.…”
Section: Evaluation and Subjective Experience Of Group Workmentioning
confidence: 99%